Effect of sprinkler-based water application in mitigating ammonia emissions from beef cattle feedyards - Myeongseong Lee; Brent W. Auvermann; K. Jack Bush; Greg B. Ferguson; Carolina B. Brandani; Kenneth D. Casey; Vinícius N. Gouvêa; Jason K. Smith; Luis O. Tedeschi; Jacek A. Koziel (Biosystems Engineering, 2026)

Why toxin genes are not enough: regulatory and life-cycle controls shape dinoflagellate toxicity - Yue Jiang; Na Wang; Bernd Krock; Kenneth Mertens; Zhun Li; Hyeon Ho Shin; Nihal G. Shams El-Din; Ophélie David; Iria Garcia Moreiras; Eduardo Pérez-Vega; Kirsty Smith; Haifeng Gu (Harmful Algae, 2026)

Spinal cord lesion characteristics and early standing ability with and without epidural stimulation - Enrico Rejc; Andrew C. Smith; Claudia A. Angeli; Kenneth A. Weber II; M. J. Negahdar; Katherine Smulligan; Jordan Connor; Gail F. Forrest; Robert J. Bert; Maxwell Boakye; Susan J. Harkema (Experimental Brain Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Beyond Climate Change: The Role of Integrated Soil Fertility Management for Sustaining Future Maize Yield in Sub‐Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Johan Six; Moritz Laub; Alex C. Ruane; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; et al. (Global Change Biology, 2026)
Climate change is projected to exacerbate food insecurity in sub‐Saharan Africa (SSA) by reducing crop yields and soil fertility. Many climate change impact studies in SSA have overlooked long‐term effects of soil fertility on crop yield. We evaluated maize yields under different scenarios of soil fertility (using soil organic carbon as a proxy) and climate change (considering changes in temperature, rainfall, and CO 2 ) at four sites in SSA. Using an ensemble of 15 calibrated soil‐crop models, we found a strong consensus that, without fertilization, soil fertility declines over time, impacting maize yields more strongly than changes in temperature, rainfall, or CO 2 . The model ensemble indicated that when accounting for soil fertility changes, the yield benefits of combined application of organic and mineral inputs increase over time, even under climate change. These findings highlight the importance of considering long‐term change in soil fertility when assessing impacts of climate change and integrated nutrient management on crop production in SSA.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Inter-comparison of soybean models for simulation of evapotranspiration under rainfed and irrigated conditions - Kritika Kothari; Andrew Suyker; Rafael Battisti; Kenneth J. Boote; Sotirios Archontoulis; Julie Constantin; Santiago V. Cuadra; Philippe Debaeke; Elvis F. Elli; Babacar Faye; David Fleisher; Brian Grant; et al. (Agricultural and Forest Meteorology, 2026)

Beyond strength: dietary nitrate augments self-selected functional mobility after resistance training in middle-aged adults - Brandon M. Peoples; Mason C. McIntosh; Kenneth D. Harrison; Bria R. Smith; Keven G. Santamaria Guzman; Silvia E. Campos-Vargas; Damaris C. Cifuentes; Breanna J. Mueller; Andreas N. Kavazis; Darren T. Beck; Michael D. Roberts; Jaimie A. Roper (GeroScience, 2025)
This study aimed to assess whether dietary nitrate supplementation with resistance training (RT) augments gait performance and functional mobility in inactive middle-aged and older adults. We hypothesized that combining nitrate-rich beetroot juice (BRJ) with RT would yield improvements in gait and functional mobility compared to RT with nitrate-depleted beetroot juice placebo (PLA) supplementation. In this 12-week, randomized, double-blind, placebo-controlled pilot trial, 28 healthy, inactive adults (56 ± 7 years) were assigned to either a BRJ (~ 12.8 mmol nitrate/day) or PLA group while completing a supervised, full-body RT program (2×/week). Pre- and post-intervention assessments included the instrumented stand and walk (iSAW), 6-min walk test (i6MWT), and timed up and go (iTUG) tests. Supplement adherence, training compliance, and volume were equivalent between groups. ANCOVA analyses controlling baseline values revealed significant between-group differences favoring the BRJ group for gait speed (adjusted means: 1.38 vs 1.27 m/s, p = .010), stride length ( p < .001), and iTUG duration ( p < .05). Within-group analyses confirmed that the BRJ group experienced significant improvements in gait speed ( p < 0.001) and iTUG duration ( p < 0.05), while the PLA group showed no functional changes, indicating that 12 weeks of RT alone was insufficient to improve functional mobility in our sample despite equivalent training responses ( p > .05). In our middle-aged sample, supplementing dietary nitrate alongside RT led to clinically meaningful improvements in functional mobility during self-selected conditions, exceeding the gains from 12 weeks of twice-weekly RT alone. Preliminary descriptive analyses revealed sex-specific group-level differences that might suggest emerging trends. Although no inferential statistics were conducted, the patterns provide potential directions for future research investigating the effects of RT in middle-aged adults. Graphical Abstract

Thirty years of arboreal wildlife trends in an African rainforest under evolving threats and researchers' presence - Bastien Dehaudt; Ruksan Bose; Jean Jacques Avoto; Stephanie Brittain; Tom Bruce; Emily K. Chen; Francis A. Forzi; Britta D. Hardesty; Kimberly M. Holbrook; Aaron M. Lamperti; V. Thomas Parker; John R. Poulsen; et al. (Biological Conservation, 2025)

Human‐Mediated Dispersal Routes Structure Sahara Mustard Genomics - Daniel E. Winkler; Kenneth J. Chapin; Waffa M. Amer; Matthew Augé; Marie‐Claude Bon; Massimo Cristofaro; Olivier François; J. David Garmon; Brandon S. Gaut; Javid Kashefi; Francesca Marini; René Sforza; et al. (Molecular Ecology, 2025)
Humans have facilitated the spread and evolution of invasive species, a pattern that has accelerated with the globalisation of trade and societal development. Consequently, the invasiveness of a species may be determined not only by how many propagules and which genotypes are introduced, but also by its evolutionary history and how humans have interacted with it. Here, we document the population structure and movement of Sahara mustard ( Brassica tournefortii ) within its native range and its invaded U.S. and Australian ranges. We evaluated 312 individuals spanning 31 sites. We found that Sahara mustard has likely undergone substantial mixing within its native range, with genotypes from Egypt potentially representing a human‐created connection between North African, European and West Asian genotypes. Our results suggest Egypt—and perhaps closely related populations in Morocco and France—as the likely origin of invasive U.S. populations. Australian accessions appear most closely related to those from Qatar and may have acted as a bridgehead and potential source of the most‐recently introduced U.S. population. Further, agricultural varieties from Pakistan and India represent a mix of genotypes from the western part of the species' native range and the eastern site in Qatar. We also identified evidence of mixing of some accessions of crop wild relatives. Nearly all populations sampled display excess heterozygosity and negative inbreeding coefficients, likely indicative of selection and potential admixture with other cultivated Brassica species. Overall, we reconstructed the probable invasion history of Sahara mustard, inferring significant human‐mediated movement of the species within and beyond its native distribution.

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Transformations of particulate organic matter from the surface to the abyssal plain in the North Pacific as inferred from compound-specific stable isotope and microbial community analyses - Lee C. Miller; Hilary G. Close; Kalina C. Grabb; Christine L. Huffard; Fuyan Li; David M. Karl; Kenneth L. Smith; Edward F. DeLong; Claudia R. Benitez-Nelson; Jeffrey C. Drazen; Brian N. Popp (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Verbal fluency dual-tasks show greater age-related cognitive-motor interference: a meta-analysis of walking performance - Kenneth Harrison; Keven Santa-Maria Guzman; Brandon M. Peoples; Silvia Campos-Vargas; Bria R. Smith; Damaris C. Cifuentes; Grace Greer; Kristina A. Neely; Jaimie A. Roper (Experimental Brain Research, 2025)
A substantial body of literature has examined gait during cognitive dual-tasking in younger and older adults. However, it remains unclear how, and to what extent, different cognitive tasks uniquely influence gait. This meta-analysis quantified age-related differences in gait speed during dual-task walking. Importantly, we examined cognitive task as a potential moderator. We searched Web of Science for studies comparing young and older adults during single-task and dual-task walking conditions. Twenty-two studies met the inclusion criteria, representing 544 young adults (mean age range: 20–31 years) and 511 older adults (mean age range: 62–85 years). Studies employed primarily serial subtraction tasks (n = 12) and verbal fluency tasks (n = 8); however, one study used digit vigilance, and another used a texting paradigm during walking. Random-effects meta-analysis using standardized mean differences (Hedges' g) revealed a significant overall effect (g = −0.2612, 95% CI [−0.4914, –0.0310], p = 0.0261), indicating greater dual-task costs in older adults compared to younger adults with a small to medium effect size. Substantial heterogeneity was observed across studies (I 2 = 66.53%, p < 0.0001). Subgroup analysis demonstrated that verbal fluency tasks produced a larger and statistically significant age-related difference (g = −0.4744, 95% CI [−0.8712, −0.0777], p = 0.0191), while serial subtraction tasks showed smaller, non-significant effects (g = −0.1412, p = 0.3474). These findings suggest that verbal fluency creates unique neural resource competition in older adults, involving prefrontal, cerebellar, and basal ganglia circuits that support both language production and gait control. The task-specific vulnerability to verbal fluency, and not serial subtraction, provides evidence for age-related changes in cognitive-motor integration. Rehabilitation strategies targeting executive functions may be effective for maintaining mobility in aging populations.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Limited persistence of the heat-tolerant zooxanthella, Durusdinium trenchii, in corals transplanted to a barrier reef where it is rare among natal colonies - Kira E. Turnham; Allison M. Lewis; Dustin W. Kemp; Mark E. Warner; Drew F. Wham; Robin T. Smith; Kenneth Hoadley; Patrick L. Colin; Yimnang Golbuu; Todd C. LaJeunesse (Coral Reefs, 2025)

Inter-comparison of soybean models for the simulation of evapotranspiration in a humid continental climate - Evandro H. Figueiredo Moura da Silva; Kritika Kothari; Elizabeth Pattey; Rafael Battisti; Kenneth J. Boote; Sotirios V. Archontoulis; Santiago Vianna Cuadra; Babacar Faye; Brian Grant; Gerrit Hoogenboom; Qi Jing; Fábio R. Marin; et al. (Agricultural and Forest Meteorology, 2025)

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

The seasonal patterns of hydrographic and biogeochemical variables in the Ross Sea: A BGC-Argo analysis - Ruobing Cao; Walker O. Smith; Yisen Zhong; Stephen Riser; Kenneth S. Johnson; Lynne Talley (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

What is normal age-related thigh muscle composition among 45- to 84-year-old adults from the UK Biobank study - David B. Anderson; Aaron J. Beach; Lingxiao Chen; Henry J. Feng; Marnee J. McKay; Zachary A. Smith; Kenneth A. Weber; Evert Onno Wesselink; James M. Elliott (GeroScience, 2024)
A loss of skeletal muscle mass and an increase in intramuscular fat are known to occur as we enter middle and older age, but the expected changes or normative values have remained unknown. The primary reason for this is that imaging studies are difficult and expensive to conduct, and consequently, the sample sizes have remained small. The development of the UK Biobank which provides access to a large magnetic resonance imaging (MRI) data set of more than 50,000 participants provides an opportunity to finally address this question of normative values for each age group. The study’s primary aim was to determine the age-related changes in thigh muscle composition (e.g., thigh fat-free muscle volume and intramuscular fat) between the ages of 45 and 84 years. The second aim was to analyse associations between thigh fat-free muscle volume and intramuscular fat with lifestyle behaviours (smoking, alcohol consumption, and physical activity), leg pain, and bone mineral density. Fifty thousand three hundred thirty-two participants were included in the study. Total fat-free thigh muscle declined between the ages of 45 and 84 years, while intramuscular fat of the thigh continued to increase. The changes were stable between these age groups. The mean volume of fat-free muscle ranged from 11.16 (SD: 1.40) to 13.26 L (SD: 1.85) in adult males and 7.60 (SD: 0.97) to 8.80 L (SD 1.29) in females between the ages of 45 and 84 years. For intramuscular fat, the change among women was from 6.94% (SD: 1.59) in the 45 to 54 years age bracket to 8.83% (SD: 1.92) in the 75 to 84 age bracket, while for men, it was 5.83% (SD: 1.30) in the 45 to 54 age bracket to 7.85% (SD 1.89) in the 75 to 84 age bracket. The total fat-free muscle volume and intramuscular fat percentage provided can be used for the purpose of reference standards or normative values for adults in the age groups provided. Fat-free muscle and intramuscular fat were found to be associated with a range of health, activity, and leg pain outcomes, and these should be investigated in a follow-up longitudinal imaging study.

The diversity, distribution, and temporal stability of coral ‘zooxanthellae’ on a pacific reef: from the scale of individual colonies to across the host community - Allison M. Lewis; Caleb C. Butler; Kira E. Turnham; Drew F. Wham; Kenneth D. Hoadley; Robin T. Smith; Dustin W. Kemp; Mark E. Warner; Todd C. LaJeunesse (Coral Reefs, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Forest carbon uptake as influenced by snowpack and length of photosynthesis season in seasonally snow-covered forests of North America - Julia C. Yang; David R. Bowling; Kenneth R. Smith; Lewis Kunik; Brett Raczka; William R.L. Anderegg; Michael Bahn; Peter D. Blanken; Andrew D. Richardson; Sean P. Burns; Gil Bohrer; Ankur R. Desai; et al. (Agricultural and Forest Meteorology, 2024)

A circumpolar study unveils a positive non‐linear effect of temperature on arctic arthropod availability that may reduce the risk of warming‐induced trophic mismatch for breeding shorebirds - Aurélie Chagnon‐Lafortune; Éliane Duchesne; Pierre Legagneux; Laura McKinnon; Jeroen Reneerkens; Nicolas Casajus; Kenneth F. Abraham; Élise Bolduc; Glen S. Brown; Stephen C. Brown; H. River Gates; Olivier Gilg; et al. (Global Change Biology, 2024)
Seasonally abundant arthropods are a crucial food source for many migratory birds that breed in the Arctic. In cold environments, the growth and emergence of arthropods are particularly tied to temperature. Thus, the phenology of arthropods is anticipated to undergo a rapid change in response to a warming climate, potentially leading to a trophic mismatch between migratory insectivorous birds and their prey. Using data from 19 sites spanning a wide temperature gradient from the Subarctic to the High Arctic, we investigated the effects of temperature on the phenology and biomass of arthropods available to shorebirds during their short breeding season at high latitudes. We hypothesized that prolonged exposure to warmer summer temperatures would generate earlier peaks in arthropod biomass, as well as higher peak and seasonal biomass. Across the temperature gradient encompassed by our study sites (>10°C in average summer temperatures), we found a 3‐day shift in average peak date for every increment of 80 cumulative thawing degree‐days. Interestingly, we found a linear relationship between temperature and arthropod biomass only below temperature thresholds. Higher temperatures were associated with higher peak and seasonal biomass below 106 and 177 cumulative thawing degree‐days, respectively, between June 5 and July 15. Beyond these thresholds, no relationship was observed between temperature and arthropod biomass. Our results suggest that prolonged exposure to elevated temperatures can positively influence prey availability for some arctic birds. This positive effect could, in part, stem from changes in arthropod assemblages and may reduce the risk of trophic mismatch.

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Impact of assimilation of absolute dynamic topography on Arctic Ocean circulation - Gregory C. Smith; Charlie Hébert-Pinard; Audrey-Anne Gauthier; François Roy; Kenneth Andrew Peterson; Pierre Veillard; Yannice Faugère; Sandrine Mulet; Miguel Morales Maqueda (Frontiers in Marine Science, 2024)
The ocean circulation is typically constrained in operational analysis and forecasting systems through the assimilation of sea level anomaly (SLA) retrievals from satellite altimetry. This approach has limited benefits in the Arctic Ocean and surrounding seas due to data gaps caused by sea ice coverage. Moreover, assimilation of SLA in seasonally ice-free regions may be negatively affected by the quality of the Mean Sea Surface (MSS) used to derive the SLA. Here, we use the Regional Ice Ocean Prediction System (RIOPS) to investigate the impact of assimilating Absolute Dynamic Topography (ADT) fields on the circulation in the Arctic Ocean. This approach avoids the use of a MSS and additionally provides information on sea level in ice covered regions using measurements across leads (openings) in the sea ice. RIOPS uses a coupled ice-ocean model on a 3-4 km grid-resolution pan-Arctic domain together with a multi-variate reduced-order Kalman Filter. The system assimilates satellite altimetry and sea surface temperature together with in situ profile observations. The background error is modified to match the spectral characteristics of the ADT fields, which contain less energy at small scales than traditional SLA due to filtering applied to reduce noise originating in the geoid product used. A series of four-year reanalyses demonstrate significant reductions in innovation statistics with important impacts across the Arctic Ocean. Results suggest that the assimilation of ADT can improve circulation and sea ice drift in the Arctic Ocean, and intensify volume transports through key Arctic gateways and resulting exchanges with the Atlantic Ocean. A reanalysis with a modified Mean Dynamic Topography (MDT) is able to reproduce many of the benefits of the ADT but does not capture the enhanced transports. Assimilation of SLA observations from leads in the sea ice appears to degrade several circulation features; however, these results may be sensitive to errors in MDT. This study highlights the large uncertainties that exist in present operational ocean forecasting systems for the Arctic Ocean due to the relative paucity and reduced quality of observations compared to ice-free areas of the Global Ocean. Moreover, this underscores the need for dedicated and focused efforts to address this critical gap in the Global Ocean Observing System.

Sudden peak in tetrodotoxin in French oysters during the summer of 2021: Source investigation using microscopy, metabarcoding and droplet digital PCR - Laura Biessy; John K. Pearman; Kenneth Neil Mertens; Damien Réveillon; Véronique Savar; Philipp Hess; Hannah Hampton; Lucy Thompson; Luc Lebrun; Aouregan Terre-Terrillon; Kirsty F. Smith (Toxicon, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Evaluating differences among crop models in simulating soybean in-season growth - Kritika Kothari; Rafael Battisti; Kenneth J. Boote; Sotirios V. Archontoulis; Adriana Confalone; Julie Constantin; Santiago V. Cuadra; Philippe Debaeke; Babacar Faye; Brian Grant; Gerrit Hoogenboom; Qi Jing; et al. (Field Crops Research, 2024)

Long-term soil organic carbon and crop yield feedbacks differ between 16 soil-crop models in sub-Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; Juraj Balkovic; Bruno Basso; Arti Bhatia; et al. (European Journal of Agronomy, 2024)

Anti-cytomegalovirus antibody levels stratify human immune profiles across the lifespan - Makiko Watanabe; Lisa Davidson; Patricia Smith; Peter F. Castellucio; Mladen Jergovic; Jennifer L. Uhrlaub; Megan J. Smithey; Lori E. Fantry; Brett Dechambre; Rachel C. Wilson; Kenneth C. Knox; Jie Ren; et al. (GeroScience, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Adapting the CROPGRO Perennial Forage model to predict growth and development of Pensacola bahiagrass - Hunter D. Smith; Chris H. Wilson; Stuart J. Rymph; Erick R.S. Santos; Kenneth J. Boote (Field Crops Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Impact of phenanthrene co-administration on the toxicokinetics of benzo[a]pyrene in humans. UPLC-accelerator mass spectrometry following oral microdosing - Monica L. Vermillion Maier; Lisbeth K. Siddens; Jamie M. Pennington; Sandra L. Uesugi; Edwin M. Labut; Emily A. Vertel; Kim A. Anderson; Lane G. Tidwell; Susan C. Tilton; Ted J. Ognibene; Kenneth W. Turteltaub; Jordan N. Smith; et al. (Chemico-Biological Interactions, 2023)

Snow-corrected vegetation indices for improved gross primary productivity assessment in North American evergreen forests - Ran Wang; David R. Bowling; John A. Gamon; Kenneth R. Smith; Rong Yu; Gabriel Hmimina; Masahito Ueyama; Asko Noormets; Thomas E. Kolb; Andrew D. Richardson; Charles P.A. Bourque; Rosvel Bracho; et al. (Agricultural and Forest Meteorology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Natural attenuation of uranium in a fluvial Wetland: Importance of hydrology and speciation - Daniel I. Kaplan; Ronald J. Smith; Connor J. Parker; Kimberly A. Roberts; Pieter Hazenberg; Juan Morales; Edward J. O'Loughlin; Maxim I. Boyanov; Pamela Weisenhorn; Kenneth M. Kemner; Brian A. Powell (Applied Geochemistry, 2023)

Evaluation of plug-in hybrid vehicles in real-world conditions by simulation - Roland Dauphin; Vivien Prevost; Philippe Degeilh; Joris Melgar; Corrado Fittavolini; Alastair Smith; Cyrille Callu; Sofia Chrysafi; Renate Uitz-Choi; Kenneth Kar (Transportation Research Part D: Transport and Environment, 2023)

Gross and histological features associated with umbilical cord torsion in equine abortions - Jessica M Roach; Alastair K Foote; Kristien L Verheyen; Jill Bryan; Kenneth C Smith; Amanda M de Mestre (Journal of Equine Veterinary Science, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Differences in leaf gas exchange strategies explain Quercus rubra and Liriodendron tulipifera intrinsic water use efficiency responses to air pollution and climate change - Justin M. Mathias; Kenneth R. Smith; Kristin E. Lantz; Keanan T. Allen; Marvin J. Wright; Afsoon Sabet; Kristina J. Anderson‐Teixeira; Richard B. Thomas (Global Change Biology, 2023)
Trees continuously regulate leaf physiology to acquire CO 2 while simultaneously avoiding excessive water loss. The balance between these two processes, or water use efficiency (WUE), is fundamentally important to understanding changes in carbon uptake and transpiration from the leaf to the globe under environmental change. While increasing atmospheric CO 2 (iCO 2 ) is known to increase tree intrinsic water use efficiency (iWUE), less clear are the additional impacts of climate and acidic air pollution and how they vary by tree species. Here, we couple annually resolved long‐term records of tree‐ring carbon isotope signatures with leaf physiological measurements of Quercus rubra ( Quru ) and Liriodendron tulipifera ( Litu ) at four study locations spanning nearly 100 km in the eastern United States to reconstruct historical iWUE, net photosynthesis ( A net ), and stomatal conductance to water ( g s ) since 1940. We first show 16%–25% increases in tree iWUE since the mid‐20th century, primarily driven by iCO 2 , but also document the individual and interactive effects of nitrogen (NO x ) and sulfur (SO 2 ) air pollution overwhelming climate. We find evidence for Quru leaf gas exchange being less tightly regulated than Litu through an analysis of isotope‐derived leaf internal CO 2 (C i ), particularly in wetter, recent years. Modeled estimates of seasonally integrated A net and g s revealed a 43%–50% stimulation of A net was responsible for increasing iWUE in both tree species throughout 79%–86% of the chronologies with reductions in g s attributable to the remaining 14%–21%, building upon a growing body of literature documenting stimulated A net overwhelming reductions in g s as a primary mechanism of increasing iWUE of trees. Finally, our results underscore the importance of considering air pollution, which remains a major environmental issue in many areas of the world, alongside climate in the interpretation of leaf physiology derived from tree rings.

Targeted metabolomics reveals plasma biomarkers and metabolic alterations of the aging process in healthy young and older adults - Paniz Jasbi; Janko Nikolich-Žugich; Jeffrey Patterson; Kenneth S. Knox; Yan Jin; George M. Weinstock; Patricia Smith; Homer L. Twigg; Haiwei Gu (GeroScience, 2023)

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Silicone passive sampling used to identify novel dermal chemical exposures of firefighters and assess PPE innovations - Emily M. Bonner; Gavin P. Horn; Denise L. Smith; Steve Kerber; Kenneth W. Fent; Lane G. Tidwell; Richard P. Scott; Kaley T. Adams; Kim A. Anderson (International Journal of Hygiene and Environmental Health, 2023)

Benzo[a]pyrene toxicokinetics in humans following dietary supplementation with 3,3′-diindolylmethane (DIM) or Brussels sprouts - Monica L. Vermillion Maier; Lisbeth K. Siddens; Jamie M. Pennington; Sandra L. Uesugi; Susan C. Tilton; Emily A. Vertel; Kim A. Anderson; Lane G. Tidwell; Ted J. Ognibene; Kenneth W. Turteltaub; Jordan N. Smith; David E. Williams (Toxicology and Applied Pharmacology, 2023)

Metabolic and molecular responses of human patellar tendon to concentric- and eccentric-type exercise in youth and older age - Hannah Crossland; Matthew S. Brook; Jonathan I. Quinlan; Martino V. Franchi; Bethan E. Phillips; Daniel J. Wilkinson; Constantinos N. Maganaris; Paul L. Greenhaff; Nathaniel J. Szewczyk; Kenneth Smith; Marco V. Narici; Philip J. Atherton (GeroScience, 2023)
Exercise training can induce adaptive changes to tendon tissue both structurally and mechanically; however, the underlying compositional changes that contribute to these alterations remain uncertain in humans, particularly in the context of the ageing tendon. The aims of the present study were to determine the molecular changes with ageing in patellar tendons in humans, as well as the responses to exercise and exercise type (eccentric (ECC) and concentric (CON)) in young and old patellar tendon. Healthy younger males (age 23.5 ± 6.1 years; n = 27) and older males (age 68.5 ± 1.9 years; n = 27) undertook 8 weeks of CON or ECC training (3 times per week; at 60% of 1 repetition maximum (1RM)) or no training. Subjects consumed D 2 O throughout the protocol and tendon biopsies were collected after 4 and 8 weeks for measurement of fractional synthetic rates (FSR) of tendon protein synthesis and gene expression. There were increases in tendon protein synthesis following 4 weeks of CON and ECC training ( P < 0.01; main effect by ANOVA), with no differences observed between young and old males, or training type. At the transcriptional level however, ECC in young adults generally induced greater responses of collagen and extracellular matrix-related genes than CON, while older individuals had reduced gene expression responses to training. Different training types did not appear to induce differential tendon responses in terms of protein synthesis, and while tendons from older adults exhibited different transcriptional responses to younger individuals, protein turnover changes with training were similar for both age groups.

Occurrence of Z-drugs, benzodiazepines, and ketamine in wastewater in the United States and Mexico during the Covid-19 pandemic - Sangeet Adhikari; Rahul Kumar; Erin M. Driver; Devin A. Bowes; Keng Tiong Ng; Juan Eduardo Sosa-Hernandez; Mariel Araceli Oyervides-Muñoz; Elda M. Melchor-Martínez; Manuel Martínez-Ruiz; Karina G. Coronado-Apodaca; Ted Smith; Aruni Bhatnagar; et al. (Science of The Total Environment, 2023)

Correction to: Cancer Risk and Diesel Exhaust Exposure Among Railroad Workers - Paul E. Rosenfeld; Kenneth R. Spaeth; Ryan Hallman; Rachel Bressler; Graham C. Smith (Water, Air, & Soil Pollution, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

The Combined Oral Stable Isotope Assessment of Muscle (COSIAM) reveals D-3 creatine derived muscle mass as a standout cross-sectional biomarker of muscle physiology vitality in older age - Jessica Cegielski; Matthew S. Brook; Bethan E. Phillips; Catherine Boereboom; Amanda Gates; John F. R. Gladman; Kenneth Smith; Daniel J. Wilkinson; Philip J. Atherton (GeroScience, 2022)
Validated diagnostics of skeletal muscle vitality could benefit clinical and basic science in terms of mechanistic insights and in determining the efficacy of interventions, e.g. exercise/pharmaceuticals/nutrients. We recently developed a Combined Oral Assessment of Muscle (COSIAM) that can be used to simultaneously quantify whole-body muscle mass (WBMM), muscle protein synthesis (MPS) and muscle protein breakdown (MPB). Here, we aimed to establish, in a cross-sectional fashion, links between COSIAM parameters and established aspects of muscle function. We recruited 37 healthy older adults (male (M):female (F) (21/16); 72 ± 5 y)) into a 3-day trial. Subjects consumed D 3 -creatine (D 3 -Cr dilution to assess WBMM), D 2 O (MPS by incorporation of alanine) and D 3 -3-methylhistidine (D 3 -MH dilution to assess MPB). A biopsy at day 3 was used to determine MPS, and blood/urine samples were collected to determine D 3 -Cr/D 3 -MH dilution for WBMM and MPB. Physiological measures of muscle mass (e.g. DXA/ultrasound) and function (e.g. handgrip strength, maximum voluntary contraction (MVC), one-repetition maximum (1-RM)) were ascertained. A stepwise linear regression approach was used to address links between facets of COSIAM (MPS, MPB, WBMM) and muscle physiology. Despite expected differences in muscle mass, there were no significant differences in MPS or MPB between sexes. WBMM as measured using D 3 -Cr positively correlated with DXA-derived lean body mass (LBM) and appendicular LBM (ABLM). Stepwise linear regression was used to assess which combination of MPS, MPB, D 3 -Cr and absolute synthesis rate (ASR) best predicted physiological measures of muscle health in these older adults. D 3 -Cr WBMM alone was the best predictor of handgrip, 1RM and MVC, and outperformed more traditional measures of muscle mass by DXA. The COSIAM approach substantiates D 3 -Cr as a robust biomarker of multiple muscle physiology health biomarkers. Future work using COSIAM should focus upon how and which parameters it can inform upon in relation to disease progression and the efficacy of interventions.

Front-Loaded Versus Low-Intermittent Phenobarbital Dosing for Benzodiazepine-Resistant Severe Alcohol Withdrawal Syndrome - Poorvi Shah; Kati L. Stegner-Smith; Mohamad Rachid; Tabassum Hanif; Kenneth W. Dodd (Journal of Medical Toxicology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Cancer Risk and Diesel Exhaust Exposure Among Railroad Workers - Paul E. Rosenfeld; Kenneth R. Spaeth; Ryan Hallman; Rachel Bressler; Graham C. Smith (Water, Air, & Soil Pollution, 2022)
Inhalation exposure to diesel exhaust in the railroad work environment causes significant and quantifiable cancer risks to many railroad workers. Diesel exhaust has been identified as a known human carcinogen by the International Agency for Research on Cancer (“IARC”) and as a potential carcinogen by the United States Environmental Protection Agency (“USEPA”), the California Environmental Protection Agency’s Office of Environmental Health Hazard Assessment (“OEHHA”), and the National Institute for Occupational Safety & Health (“NIOSH”). Peer-reviewed literature defines the ambient air concentrations of diesel exhaust for several railroad occupations as being above environmental background levels. This study uses diesel exhaust concentrations in the railroad work environment in conjunction with the USEPA’s Integrated Risk Information System (“IRIS”) risk assessment methodology to quantify the cancer risk posed to railroad workers due to occupational inhalation exposure to diesel exhaust. NIOSH Bulletin 68 (2017) states that there is “no known safe level” of exposure to carcinogens and recommends an evaluation of the USEPA’s IRIS guidance to evaluate quantitative risk assessment of human exposure to occupational carcinogens. This is the first study to utilize USEPA methodology to calculate the excess lung cancer risk caused by railroad workers’ cumulative exposure to diesel exhaust.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Spinal cord imaging markers and recovery of standing with epidural stimulation in individuals with clinically motor complete spinal cord injury - Andrew C. Smith; Claudia A. Angeli; Beatrice Ugiliweneza; Kenneth A. Weber; Robert J. Bert; Mohammadjavad Negahdar; Samineh Mesbah; Maxwell Boakye; Susan J. Harkema; Enrico Rejc (Experimental Brain Research, 2022)

Six weeks of high-intensity interval training enhances contractile activity induced vascular reactivity and skeletal muscle perfusion in older adults - Philip J. J. Herrod; Philip J. Atherton; Kenneth Smith; John P. Williams; Jonathan N. Lund; Bethan E. Phillips (GeroScience, 2021)
Impairments in muscle microvascular function are associated with the pathogenesis of sarcopenia and cardiovascular disease. High-intensity interval training (HIIT) is an intervention by which a myriad of beneficial skeletal muscle/cardiovascular adaptations have been reported across age, including capillarisation and improved endothelial function. Herein, we hypothesised that HIIT would enhance muscle microvascular blood flow and vascular reactivity to acute contractile activity in older adults, reflecting HIIT-induced vascular remodelling. In a randomised controlled-trial, twenty-five healthy older adults aged 65–85 years (mean BMI 27.0) were randomised to 6-week HIIT or a no-intervention control period of an equal duration. Measures of microvascular responses to a single bout of muscle contractions (i.e. knee extensions) were made in the m. vastus lateralis using contrast-enhanced ultrasound during a continuous intravenous infusion of Sonovue™ contrast agent, before and after the intervention period, with concomitant assessments of cardiorespiratory fitness and resting blood pressure. HIIT led to improvements in anaerobic threshold (13.2 ± 3.4 vs. 15.3 ± 3.8 ml/kg/min, P < 0.001), dynamic exercise capacity (145 ± 60 vs. 159 ± 59 W, P < 0.001) and resting (systolic) blood pressure (142 ± 15 vs. 133 ± 11 mmHg, P < 0.01). Notably, HIIT elicited significant increases in microvascular blood flow responses to acute contractile activity (1.8 ± 0.63 vs. 2.3 ± 0.8 (arbitrary contrast units (AU), P < 0.01)), with no change in any of these parameters observed in the control group. Six weeks HIIT improves skeletal muscle microvascular responsiveness to acute contractile activity in the form of active hyperaemia-induced by a single bout of resistance exercise. These findings likely reflect reports of enhanced large vessel distensibility, improved endothelial function, and muscle capillarisation following HIIT. Moreover, our findings illustrate that HIIT may be effective in mitigating deleterious alterations in muscle microvascular mediated aspects of sarcopenia.

Combined in vivo muscle mass, muscle protein synthesis and muscle protein breakdown measurement: a ‘Combined Oral Stable Isotope Assessment of Muscle (COSIAM)’ approach - Jessica Cegielski; Daniel J. Wilkinson; Matthew S. Brook; Catherine Boereboom; Bethan E. Phillips; John F. R. Gladman; Kenneth Smith; Philip J. Atherton (GeroScience, 2021)
Optimising approaches for measuring skeletal muscle mass and turnover that are widely applicable, minimally invasive and cost effective is crucial in furthering research into sarcopenia and cachexia. Traditional approaches for measurement of muscle protein turnover require infusion of expensive, sterile, isotopically labelled tracers which limits the applicability of these approaches in certain populations (e.g. clinical, frail elderly). To concurrently quantify skeletal muscle mass and muscle protein turnover i.e. muscle protein synthesis (MPS) and muscle protein breakdown (MPB), in elderly human volunteers using stable-isotope labelled tracers i.e. Methyl-[D 3 ]-creatine (D 3 -Cr), deuterium oxide (D 2 O), and Methyl-[D 3 ]-3-methylhistidine (D 3 -3MH), to measure muscle mass, MPS and MPB, respectively. We recruited 10 older males (71 ± 4 y, BMI: 25 ± 4 kg . m 2 , mean ± SD) into a 4-day study, with DXA and consumption of D 2 O and D 3 -Cr tracers on day 1. D 3 -3MH was consumed on day 3, 24 h prior to returning to the lab. From urine, saliva and blood samples, and a single muscle biopsy (vastus lateralis), we determined muscle mass, MPS and MPB. D 3 -Cr derived muscle mass was positively correlated to appendicular fat-free mass (AFFM) estimated by DXA (r = 0.69, P = 0.027). Rates of cumulative myofibrillar MPS over 3 days were 0.072%/h (95% CI, 0.064 to 0.081%/h). Whole-body MPB over 6 h was 0.052 (95% CI, 0.038 to 0.067). These rates were similar to previous literature. We demonstrate the potential for D 3 -Cr to be used alongside D 2 O and D 3 -3MH for concurrent measurement of muscle mass, MPS, and MPB using a minimally invasive design, applicable for clinical and frail populations.

Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Different functional traits among closely related algal symbionts dictate stress endurance for vital Indo‐Pacific reef‐building corals - Kenneth D. Hoadley; Daniel. T. Pettay; Allison Lewis; Drew Wham; Chris Grasso; Robin Smith; Dustin W. Kemp; Todd LaJeunesse; Mark E. Warner (Global Change Biology, 2021)
Reef‐building corals in the genus Porites are one of the most important constituents of Indo‐Pacific reefs. Many species within this genus tolerate abnormally warm water and exhibit high specificity for particular kinds of endosymbiotic dinoflagellates that cope with thermal stress better than those living in other corals. Still, during extreme ocean heating, some Porites exhibit differences in their stress tolerance. While corals have different physiological qualities, it remains unknown whether the stability and performance of these mutualisms is influenced by the physiology and genetic relatedness of their symbionts. We investigated two ubiquitous Pacific reef corals, Porites rus and Porites cylindrica , from warmer inshore and cooler offshore reef systems in Palau. While these corals harbored a similar kind of symbiont in the genus Cladocopium (within the ITS2 C15 subclade), rapidly evolving genetic markers revealed evolutionarily diverged lineages corresponding to each Porites species living in each reef habitat. Furthermore, these closely related Cladocopium lineages were differentiated by their densities in host tissues, cell volume, chlorophyll concentration, gross photosynthesis, and photoprotective pathways. When assessed using several physiological proxies, these previously undifferentiated symbionts contrasted in their tolerance to thermal stress. Symbionts within P . cylindrica were relatively unaffected by exposure to 32℃ for 14 days, whereas P . rus colonies lost substantial numbers of photochemically compromised symbionts. Heating reduced the ability of the offshore symbiont associated with P . rus to translocate carbon to the coral. By contrast, high temperatures enhanced symbiont carbon assimilation and delivery to the coral skeleton of inshore P . cylindrica . This study indicates that large physiological differences exist even among closely related symbionts, with significant implications for thermal susceptibility among reef‐building Porites .

Muscle and tendon adaptations to moderate load eccentric vs. concentric resistance exercise in young and older males - Jonathan Iain Quinlan; Martino Vladimiro Franchi; Nima Gharahdaghi; Francesca Badiali; Susan Francis; Andrew Hale; Bethan Eileen Phillips; Nathaniel Szewczyk; Paul Leonard Greenhaff; Kenneth Smith; Constantinos Maganaris; Phillip James Atherton; et al. (GeroScience, 2021)
Resistance exercise training (RET) is well-known to counteract negative age-related changes in both muscle and tendon tissue. Traditional RET consists of both concentric (CON) and eccentric (ECC) contractions; nevertheless, isolated ECC contractions are metabolically less demanding and, thus, may be more suitable for older populations. However, whether submaximal (60% 1RM) CON or ECC contractions differ in their effectiveness is relatively unknown. Further, whether the time course of muscle and tendon adaptations differs to the above is also unknown. Therefore, this study aimed to establish the time course of muscle and tendon adaptations to submaximal CON and ECC RET. Twenty healthy young (24.5 ± 5.1 years) and 17 older males (68.1 ± 2.4 years) were randomly allocated to either isolated CON or ECC RET which took place 3/week for 8 weeks. Tendon biomechanical properties, muscle architecture and maximal voluntary contraction were assessed every 2 weeks and quadriceps muscle volume every 4 weeks. Positive changes in tendon Young’s modulus were observed after 4 weeks in all groups after which adaptations in young males plateaued but continued to increase in older males, suggesting a dampened rate of adaptation with age. However, both CON and ECC resulted in similar overall changes in tendon Young’s modulus, in all groups. Muscle hypertrophy and strength increases were similar between CON and ECC in all groups. However, pennation angle increases were greater in CON, and fascicle length changes were greater in ECC. Notably, muscle and tendon adaptations appeared to occur in synergy, presumably to maintain the efficacy of the muscle–tendon unit.

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

Impacts of Petroleum, Petroleum Components, and Dispersants on Organisms and Populations - Steven Murawski; Martin Grosell; Cynthia Smith; Tracey Sutton; Kenneth Halanych; Richard Shaw; Charles Wilson (Oceanography, 2021)
Following the Deepwater Horizon blowout, oil, degraded oil, oil mixed with dispersants, and management responses to the spill affected a variety of Gulf of Mexico organisms. This review provides examples of various documented impacts, common patterns, and trends across organisms and/or their environments, and discusses future implications as well as directions for future research. Organism effects are generally characterized as lethal and sublethal. Sublethal can be short term, long term, or permanent and multigenerational. We present individual examples of effects on behavioral response, olfaction, vision, cardiac function, and gene shift, based on research done in laboratories, mesocosm settings, and the field. Future research should emphasize collection and analysis of routine toxicological baselines and examine how and if molecular impacts cascade up to populations. This research will require development of rapid molecular tools and testing procedures to determine exposure compared to field-relevant exposure levels and to be able to extrapolate laboratory results to the field, especially given the mosaic of differing contaminant concentrations (below, at, or exceeding critical concentrations that result in lethal or sublethal effects) occurring in the environment. Recent chemical studies have identified a detectable suite of polycyclic aromatic hydrocarbon metabolites for which there are no toxicity data; further research is needed to determine their impacts on food webs.

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Pattern and scale: evaluating generalities in crab distributions and marsh dynamics from small plots to a national scale - Kerstin Wasson; Kenneth Raposa; Monica Almeida; Kathryn Beheshti; Jeffrey A. Crooks; Anna Deck; Nikki Dix; Caitlin Garvey; Jason Goldstein; David Samuel Johnson; Scott Lerberg; Pamela Marcum; et al. (Ecology, 2019)
The generality of ecological patterns depends inextricably on the scale at which they are examined. We investigated patterns of crab distribution and the relationship between crabs and vegetation in salt marshes at multiple scales. By using consistent monitoring protocols across 15 U.S. National Estuarine Research Reserves, we were able to synthesize patterns from the scale of quadrats to the entire marsh landscape to regional and national scales. Some generalities emerged across marshes from our overall models, and these are useful for informing broad coastal management policy. We found that crab burrow distribution within a marsh could be predicted by marsh elevation, distance to creek and soil compressibility. While these physical factors also affected marsh vegetation cover, we did not find a strong or consistent overall effect of crabs at a broad scale in our multivariate model, though regressions conducted separately for each site revealed that crab burrows were negatively correlated with vegetation cover at 4 out of 15 sites. This contrasts with recent smaller‐scale studies and meta‐analyses synthesizing such studies that detected strong negative effects of crabs on marshes, likely because we sampled across the entire marsh landscape, while targeted studies are typically limited to low‐lying areas near creeks, where crab burrow densities are highest. Our results suggest that sea‐level rise generally poses a bigger threat to marshes than crabs, but there will likely be interactions between these physical and biological factors. Beyond these generalities across marshes, we detected some regional differences in crab community composition, richness, and abundance. However, we found striking differences among sites within regions, and within sites, in terms of crab abundance and relationships to marsh integrity. Although generalities are broadly useful, our findings indicate that local managers cannot rely on data from other nearby systems, but rather need local information for developing salt marsh management strategies.

Ocean FAIR Data Services - Toste Tanhua; Sylvie Pouliquen; Jessica Hausman; Kevin O’Brien; Pip Bricher; Taco de Bruin; Justin J. H. Buck; Eugene F. Burger; Thierry Carval; Kenneth S. Casey; Steve Diggs; Alessandra Giorgetti; et al. (Frontiers in Marine Science, 2019)

The American Society of Hematology (ASH) Medical Educators Institute: a Pilot Faculty Development Project for Hematology Educators - Jennifer C. Kesselheim; Charles P. Clayton; Josel Fritz; Roy E. Smith; Scott D. Gitlin; Erin Reid; Kenneth S. Zuckerman; Marc J. Kahn (Journal of Cancer Education, 2019)

Data Interoperability Between Elements of the Global Ocean Observing System - Derrick Snowden; Vardis M. Tsontos; Nils Olav Handegard; Marcos Zarate; Kevin O’ Brien; Kenneth S. Casey; Neville Smith; Helge Sagen; Kathleen Bailey; Mirtha N. Lewis; Sean C. Arms (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Broad-Scale Patterns of Soil Carbon (C) Pools and Fluxes Across Semiarid Ecosystems are Linked to Climate and Soil Texture - Kenneth R. Smith; Bonnie G. Waring (Ecosystems, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Abyssal deposit‐feeding rates consistent with the metabolic theory of ecology - Jennifer M. Durden; Brian J. Bett; Christine L. Huffard; Henry A. Ruhl; Kenneth L. Smith (Ecology, 2019)
The Metabolic Theory of Ecology ( MTE ) posits that metabolic rate controls ecological processes, such as the rate of resource uptake, from the individual‐ to the ecosystem‐scale. Metabolic rate has been found empirically to be an exponential function of whole organism body mass. We test a fundamental assumption of MTE , whether resource uptake scales to metabolism, by examining detritivores accessing a single common resource pool, an ideal study case. We used an existing empirical model of ingestion for aquatic deposit feeders adjusted for temperature to test whether ingestion by abyssal deposit feeders conforms to MTE ‐predicted feeding rates. We estimated the sediment deposit‐feeding rates of large invertebrates from two abyssal study sites using time‐lapse photography, and related those rates to body mass, environmental temperature, and sediment organic matter content using this framework. Ingestion was significantly related to individual wet mass, with a mass‐scaling coefficient of 0.81, with 95% confidence intervals that encompass the MTE ‐predicted value of 0.75, and the same pattern determined in other aquatic systems. Our results also provide insight into the potential mechanism through which this fundamental assumption operates. After temperature correction, both deep‐ and shallow‐water taxa might be summarized into a single mass‐scaled ingestion rate.

Mastication and enamel microstructure in Cambaytherium, a perissodactyl-like ungulate from the early Eocene of India - Wighart von Koenigswald; Kenneth D. Rose; Luke T. Holbrook; Kishor Kumar; Rajendra S. Rana; Thierry Smith (PalZ, 2018)

Intravenous Cocaine Results in an Acute Decrease in Levels of Biomarkers of Vascular Inflammation in Humans - Kamal Gupta; Rishi Sharma; Vikas Singh; Reza Masoomi; Kottarappat N. Dileepan; Jianghua He; Donald D. Smith; Buddhadeb Dawn; Kenneth Grasing (Cardiovascular Toxicology, 2018)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Evolution of Monitoring an Abyssal Time-Series Station in the Northeast Pacific Over 28 Years - Kenneth Smith; Alana Sherman; Paul McGill; Rich Henthorn; John Ferreira; Christine Huffard (Oceanography, 2017)

An urban stream can support a healthy population of coastal cutthroat trout - Brook P. Silver; J. Michael Hudson; Christian T. Smith; Kenneth Lujan; Melissa Brown; Timothy A. Whitesel (Urban Ecosystems, 2017)

Population pharmacokinetics and pharmacodynamics of IONIS-GCGRRx, an antisense oligonucleotide for type 2 diabetes mellitus: a red blood cell lifespan model - Kenneth T. Luu; Erin S. Morgan; Sanjay Bhanot; Richard Geary; Anne Smith; Claudette Bethune; Lynnetta Watts; Scott Henry; Yanfeng Wang (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Site-level importance of broadleaf deciduous trees outweighs the legacy of high nitrogen (N) deposition on ecosystem N status of Central Appalachian red spruce forests - Kenneth R. Smith; Justin M. Mathias; Brenden E. McNeil; William T. Peterjohn; Richard B. Thomas (Plant and Soil, 2016)

Comparing Measures of Estuarine Ecosystem Production in a Temperate New England Estuary - Autumn Oczkowski; Christopher W. Hunt; Kenneth Miller; Candace Oviatt; Scott Nixon; Leslie Smith (Estuaries and Coasts, 2016)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Four emerging arboviral diseases in North America: Jamestown Canyon, Powassan, chikungunya, and Zika virus diseases - Daniel M. Pastula; Daniel E. Smith; J. David Beckham; Kenneth L. Tyler (Journal of NeuroVirology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Economic impacts of climate change on water resources in the coterminous United States - James Henderson; Charles Rodgers; Russell Jones; Joel Smith; Kenneth Strzepek; Jeremy Martinich (Mitigation and Adaptation Strategies for Global Change, 2015)

WRF-Chem model estimates of equatorial Atlantic Ocean tropospheric ozone increases via June 2006 African biomass burning ozone precursor transport - Jonathan W. Smith; Gregory S. Jenkins; Kenneth E. Pickering (Journal of Atmospheric Chemistry, 2014)

Estuarine predator—prey interactions in the early life history of two eels (Anguilla rostrata and Conger oceanicus) - Victoria L. Musumeci; Kenneth W. Able; Mark C. Sullivan; Jennifer M. Smith (Environmental Biology of Fishes, 2014)

The immunopathology of ANCA-associated vasculitis - Eoin F. McKinney; Lisa C. Willcocks; Verena Broecker; Kenneth G. C. Smith (Seminars in Immunopathology, 2014)

Links between deep‐sea respiration and community dynamics - Henry A. Ruhl; Brian J. Bett; Sarah J. M. Hughes; Claudia H. S. Alt; Elizabeth J. Ross; Richard S. Lampitt; Corinne A. Pebody; Kenneth L. Smith; David S. M. Billett (Ecology, 2014)
It has been challenging to establish the mechanisms that link ecosystem functioning to environmental and resource variation, as well as community structure, composition, and compensatory dynamics. A compelling hypothesis of compensatory dynamics, known as “zero‐sum” dynamics, is framed in terms of energy resource and demand units, where there is an inverse link between the number of individuals in a community and the mean individual metabolic rate. However, body size energy distributions that are nonuniform suggest a niche advantage at a particular size class, which suggests a limit to which metabolism can explain community structuring. Since 1989, the composition and structure of abyssal seafloor communities in the northeast Pacific and northeast Atlantic have varied interannually with links to climate and resource variation. Here, for the first time, class and mass‐specific individual respiration rates were examined along with resource supply and time series of density and biomass data of the dominant abyssal megafauna, echinoderms. Both sites had inverse relationships between density and mean individual metabolic rate. We found fourfold variation in echinoderm respiration over interannual timescales at both sites, which were linked to shifts in species composition and structure. In the northeastern Pacific, the respiration of mobile surface deposit feeding echinoderms was positively linked to climate‐driven particulate organic carbon fluxes with a temporal lag of about one year, respiring ∼1–6% of the annual particulate organic carbon flux.

Squeezing information from regional climate change projections - results from a synthesis of CMIP5 results for south-east Queensland, Australia - Ian Smith; Jozef Syktus; Clive McAlpine; Kenneth Wong (Climatic Change, 2013)

Quantifying sources of error in multitemporal multisensor lake mapping - Evan A. Lyons; Yongwei Sheng; Laurence C. Smith; Junli Li; Kenneth M. Hinkel; John D. Lenters; Jida Wang (International Journal of Remote Sensing, 2013)

Recommendations for a national agenda to substantially reduce cervical cancer - Jennifer S. Smith; Noel T. Brewer; Debbie Saslow; Kenneth Alexander; Mildred R. Chernofsky; Richard Crosby; Libby Derting; Leah Devlin; Charles J. Dunton; Jeffrey Engle; Maria Fernandez; Mona Fouad; et al. (Cancer Causes & Control, 2013)

The effect of CO2 on the measurement of 220Rn and 222Rn with instruments utilising electrostatic precipitation - Derek Lane-Smith; Kenneth W. W. Sims (Acta Geophysica, 2013)

Estimated effects of climate change on flood vulnerability of U.S. bridges - Len Wright; Paul Chinowsky; Kenneth Strzepek; Russell Jones; Richard Streeter; Joel B. Smith; Jean-Marc Mayotte; Anthony Powell; Lesley Jantarasami; William Perkins (Mitigation and Adaptation Strategies for Global Change, 2012)

Islands of Ice: Influence of Free-Drifting Antarctic Icebergs on Pelagic Marine Ecosystems - Maria Vernet; Kenneth Smith; Adrián Cefarelli; John Helly; Ronald Kaufmann; Hai Lin; David Long; Alison Murray; Bruce Robison; Henry Ruhl; Timothy Shaw; Alana Sherman; et al. (Oceanography, 2012)

High altitude adaptation in Daghestani populations from the Caucasus - Luca Pagani; Qasim Ayub; Daniel G. MacArthur; Yali Xue; J. Kenneth Baillie; Yuan Chen; Iwanka Kozarewa; Daniel J. Turner; Sergio Tofanelli; Kazima Bulayeva; Kenneth Kidd; Giorgio Paoli; et al. (Human Genetics, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Coping with climate variability and climate change in La Ceiba, Honduras - Joel B. Smith; Kenneth M. Strzepek; Julio Cardini; Mario Castaneda; Julie Holland; Carlos Quiroz; Tom M. L. Wigley; Jose Herrero; Peter Hearne; John Furlow (Climatic Change, 2011)

Managed Forest Carbon Estimates for the US Greenhouse Gas Inventory, 1990—2008 - Linda S. Heath; James E. Smith; Kenneth E. Skog; David J. Nowak; Christopher W. Woodall (Journal of Forestry, 2011)
Land-use change and forestry is the major category featuring carbon sequestration in the annual US Greenhouse Gas Inventory, required by the United Nations Framework Convention on Climate Change. We describe the National Greenhouse Gas Inventory and present the sources of our data and methods and the most recent results. Forests and forest products in the United States sequestered more than −790 million metric tn of CO2 equivalent in 2008, on 253 million ha of forestland. This estimate represents a net increase in carbon, including effects of growth, harvests, or other disturbances of forest ecosystems, as well as carbon stored in harvested wood products. Both area and carbon density of these forestlands have increased since 1990, the first year estimates are required. Currently, 89% of net annual sequestration is in the forest ecosystem, and the balance is net carbon addition to harvested wood products.

Cloning and molecular analysis of a mannitol operon of phosphoenolpyruvate-dependent phosphotransferase (PTS) type from Vibrio cholerae O395 - Sanath Kumar; Kenneth P. Smith; Jody L. Floyd; Manuel F. Varela (Archives of Microbiology, 2011)

Doubling the chromosome number of bahiagrass via tissue culture - Kenneth H. Quesenberry; Judith M. Dampier; Y. Y. Lee; Rex L. Smith; Carlos A. Acuña (Euphytica, 2010)

Characterization of novel microsatellite loci for Myzomela cardinalis and M. rubrata honeyeaters, and cross-amplification in other species - Henri A. Thomassen; Kenneth C. Jones; John P. Pollinger; Thomas B. Smith (Conservation Genetics Resources, 2010)

Elucidation of antimicrobial susceptibility profiles and genotyping of Salmonella enterica isolates from clinical cases of salmonellosis in New Mexico in 2008 - Kenneth P. Smith; Jeffy George; Kathleen M. Cadle; Sanath Kumar; Steven J. Aragon; Ricardo L. Hernandez; Suzanna E. Jones; Jody L. Floyd; Manuel F. Varela (World Journal of Microbiology and Biotechnology, 2010)

A glycine-rich protein that facilitates exine formation during tomato pollen development - Kenneth J. McNeil; Alan G. Smith (Planta, 2010)

Gene expression in the brain during reovirus encephalitis - Kenneth L Tyler; J Smith Leser; Tzu L Phang; Penny Clarke (Journal of NeuroVirology, 2010)

Identification, cloning, and functional characterization of EmrD-3, a putative multidrug efflux pump of the major facilitator superfamily from Vibrio cholerae O395 - Kenneth P. Smith; Sanath Kumar; Manuel F. Varela (Archives of Microbiology, 2009)

Climate variation, carbon flux, and bioturbation in the abyssal North Pacific - Michael F. Vardaro; Henry A. Ruhl; Kenneth Jr. L. Smith (Limnology and Oceanography, 2009)
We hypothesized that seasonal and interannual climate‐mediated changes in particulate organic carbon (POC) flux would affect bioturbation and ultimately the sequestration of organic carbon in the deep sea. An 18‐yr timeseries photographic record from 4100‐m depth in the northeast Pacific Ocean showed increased abundance of Echinocrepis rostrata , a common epibenthic echinoid and bioturbator, since the late 1990s. Abundance, size, and speed data were used to estimate bioturbation potential to track long‐term changes in the volume of sediment disturbed by E. rostrata . There was no secular increase in E. rostrata bioturbation over 18 yr despite increased population size, although periodic variations in bioturbation were significantly correlated with POC flux. Expected changes in POC flux and bioturbation rates due to climate variation could lead to altered rates of carbon sequestration in deep‐sea sediments, affecting the global carbon cycle.

Role of Convective Flow in Carmustine Delivery to a Brain Tumor - Davis Yohanes Arifin; Kam Yiu Timothy Lee; Chi-Hwa Wang; Kenneth A. Smith (Pharmaceutical Research, 2009)

Evidence for the Transport of Maltose by the Sucrose Permease, CscB, of Escherichia coli - Yang Peng; Sanath Kumar; Ricardo L. Hernandez; Suzanna E. Jones; Kathleen M. Cadle; Kenneth P. Smith; Manuel F. Varela (The Journal of Membrane Biology, 2009)

Enzymatic activity and substrate specificity of recombinant tomato β-galactosidases 4 and 5 - Megumi Ishimaru; David L. Smith; Andrew J. Mort; Kenneth C. Gross (Planta, 2009)

Bypassing the abyssal benthic food web: Macrourid diet in the eastern North Pacific inferred from stomach content and stable isotopes analyses - Jeffrey C. Drazen; Brian N. Popp; C. Anela Choy; Tara Clemente; Lisa De Forest; Kenneth L. Smith (Limnology and Oceanography, 2008)
Deep‐sea fishes prey on benthic fauna and scavenge on the carcasses of surface‐living animals. Few studies have addressed the relative importance of each trophic pathway. Recent documentation of inter‐decadal fluctuations in macrourid densities in the abyssal Pacific, related to changing food supplies, hastens the need for information. We conducted stomach content and stable isotope analyses of two abyssal macrourids, carrion sources, and benthic prey, collected concurrently at 4100 m off California. Squid and fishes were the most frequent prey for Coryphaenoides armatus , with small crustaceans numerous in the diet of small specimens. The diet of Coryphaenoides yaquinae included more benthic prey such as crustaceans, polychaetes, and the holothuroid Protankyra brychia . Carrion was present in both species and it was 69% of the mass of food of large C. armatus . Carrion δ 15 N values were comparable to those in abyssal deposit feeders, but carrion was relatively enriched in 13 C, giving it a unique isotopic signature compared to benthic prey sources. The highest δ 13 C and δ 15 N values were observed in benthic shrimps and large polychaetes. The two macrourids had intermediate values, with C. armatus having slightly but significantly lower δ 15 N relative to C. yaquinae . Results of isotope mass balance suggest that carrion was the most important prey resource for both species but to a lesser extent in C. yaquinae . These two species bypass the conventional phytodetritus‐based abyssal food web for much of their nutrition. Their population dynamics may be tied more closely to fluctuations in epipelagic nekton populations through fishing effects and direct climatic forcing on top trophic levels.

NeuroMorpho.Org Implementation of Digital Neuroscience: Dense Coverage and Integration with the NIF - Maryam Halavi; Sridevi Polavaram; Duncan E. Donohue; Gail Hamilton; Jeffrey Hoyt; Kenneth P. Smith; Giorgio A. Ascoli (Neuroinformatics, 2008)

Impact of bioenergy crops in a carbon dioxide constrained world: an application of the MiniCAM energy-agriculture and land use model - Kenneth T. Gillingham; Steven J. Smith; Ronald D. Sands (Mitigation and Adaptation Strategies for Global Change, 2008)

Size–frequency dynamics of NE Pacific abyssal ophiuroids (Echinodermata: Ophiuroidea) - J. Ashley T. Booth; Henry A. Ruhl; Lawrence L. Lovell; David M. Bailey; Kenneth L. Smith (Marine Biology, 2008)

High bat (Chiroptera) diversity in the Early Eocene of India - Thierry Smith; Rajendra S. Rana; Pieter Missiaen; Kenneth D. Rose; Ashok Sahni; Hukam Singh; Lachham Singh (The Science of Nature, 2007)

B cells in glomerulonephritis: focus on lupus nephritis - Menna R. Clatworthy; Kenneth G. C. Smith (Seminars in Immunopathology, 2007)

Efficacy of intervention strategies for bioremediation of crude oil in marine systems and effects on indigenous hydrocarbonoclastic bacteria - Boyd A. McKew; Frédéric Coulon; Michail M. Yakimov; Renata Denaro; Maria Genovese; Cindy J. Smith; A. Mark Osborn; Kenneth N. Timmis; Terry J. McGenity (Environmental Microbiology, 2007)
Summary There is little information on how different strategies for the bioremediation of marine oil spills influence the key indigenous hydrocarbon‐degrading bacteria (hydrocarbonoclastic bacteria, HCB), and hence their remediation efficacy. Therefore, we have used quantitative polymerase chain reaction to analyse changes in concentrations of HCB in response to intervention strategies applied to experimental microcosms. Biostimulation with nutrients (N and P) produced no measurable increase in either biodegradation or concentration of HCB within the first 5 days, but after 15 days there was a significant increase (29%; P n ‐alkanes, and an increase of one order of magnitude in concentration of Thalassolituus (to 10 7 cells ml −1 ). Rhamnolipid bioemulsifier additions alone had little effect on biodegradation, but, in combination with nutrient additions, provoked a significant increase: 59% ( P n ‐alkane degradation by 5 days than was achieved with nutrient additions alone. The very low Alcanivorax cell concentrations in the microcosms were hardly influenced by addition of nutrients or bioemulsifier, but strongly increased after their combined addition, reflecting the synergistic action of the two types of biostimulatory agents. Bioaugmentation with Thalassolituus positively influenced hydrocarbon degradation only during the initial 5 days and only of the n ‐alkane fraction. Bioaugmentation with Alcanivorax was clearly much more effective, resulting in 73% greater degradation of n ‐alkanes, 59% of branched alkanes, and 28% of polynuclear aromatic hydrocarbons, in the first 5 days than that obtained through nutrient addition alone ( P Alcanivorax continued throughout the 30‐day period of the experiment. In addition to providing insight into the factors limiting oil biodegradation over time, and the competition and synergism between HCB, these results add weight to the use of bioaugmentation in oil pollution mitigation strategies.

Age and growth studies of chondrichthyan fishes: the need for consistency in terminology, verification, validation, and growth function fitting - Gregor M. Cailliet; Wade D. Smith; Henry F. Mollet; Kenneth J. Goldman (Environmental Biology of Fishes, 2006)

Adaptive Management of the Global Climate Problem: Bridging the Gap Between Climate Research and Climate Policy - Joseph Arvai; Gavin Bridge; Nives Dolsak; Robert Franzese; Tomas Koontz; April Luginbuhl; Paul Robbins; Kenneth Richards; Katrina Smith Korfmacher; Brent Sohngen; James Tansey; Alexander Thompson (Climatic Change, 2006)

Comparison of size‐dependent carbon, nitrate, and silicic acid uptake rates in high‐ and low‐iron waters - Valerie M. Franck; Geoffrey J. Smith; Kenneth W. Bruland; Mark A. Brzezinski (Limnology and Oceanography, 2005)
We compare the relative contribution of large phytoplankton (>5 and >10 µm) to uptake rates of carbon (C), nitrate (NO 3 − ), and dissolved silicon (Si) and uptake ratios of Si :NO and Si :C in Monterey Bay, California (a high‐iron region) with three low‐iron regions in the eastern tropical Pacific: the Costa Rica upwelling dome, Humboldt current, and Peru upwelling. We also demonstrate the effect of iron enrichment on the above parameters in the latter three regions. In Monterey Bay waters, the >5‐µm size fraction accounted on average for the majority of particulate organic C and was responsible for 92% of total C uptake, 81% of total NO 3 − uptake, and 98% of total 23 Si uptake. In contrast, in low‐iron eastern tropical Pacific waters, the >5‐µm size fraction accounted for less than half of the particulate organic C and was responsible for a substantially smaller proportion of total C and NO 3 − uptake: 27—43% for C and 34—59% for NO 3 − . Iron enrichment experiments in the eastern tropical Pacific resulted in much higher NO 3 − , C, and Si uptake rates, although increases were restricted to cells in the >5‐µm size fraction. Si:NO and Si:C uptake ratios decreased after iron addition at most locations, and decreases were a direct result of lower Si:NO 3 − and Si:C uptake ratios in the >5‐µm size fraction. Our results suggest that iron availability is a major factor regulating primary production, new production, Si uptake, and Si:NO 3 − and Si :C uptake ratios in the larger phytoplankton size classes in high‐nitrate, low‐chlorophyll (HNLC) regions in the eastern tropical Pacific.

A Method Countries Can Use to Estimate Changes in Carbon Stored in Harvested Wood Products and the Uncertainty of Such Estimates - Kenneth E. Skog; Kim Pingoud; James E. Smith (Environmental Management, 2004)

The effects of scale: variation in the APOA1/C3/A4/A5 gene cluster - Andrew G. Clark; Deborah A. Nickerson; Kenneth M. Weiss; Veikko Salomaa; Eric Boerwinkle; Stephanie M. Fullerton; Anne V. Buchanan; Vibhor A. Sonpar; Jari H. Stengrd; Joshua D. Smith; Scott L. Taylor; Christopher S. Carlson (Human Genetics, 2004)

Aminosalicylic acid reduces the antiproliferative effect of hyperglycaemia, advanced glycation endproducts and glycated basic fibroblast growth factor in cultured bovine aortic endothelial cells: Comparison with aminoguanidine - Yasotha Duraisamy; John Gaffney; Mark Slevin; Christopher A. Smith; Kenneth Williamson; Nessar Ahmed (Molecular and Cellular Biochemistry, 2003)

Prostate Carcinoma Skeletal Metastases: Cross-talk between Tumor and Bone - Evan T. Keller; Jian Zhang; Carlton R. Cooper; Peter C. Smith; Laurie K. McCauley; Kenneth J. Pienta; Russell S. Taichman (Cancer and Metastasis Reviews, 2001)

Iron and macronutrients in California coastal upwelling regimes: Implications for diatom blooms - Kenneth W. Bruland; Eden L. Rue; Geoffrey J. Smith (Limnology and Oceanography, 2001)
The supply of iron, relative to that of the macronutrients nitrate, phosphate, and silicic acid, plays a critical role in allowing extensive diatom blooms to develop in coastal upwelling regimes. The presence or absence of a broad continental shelf influences the supply of iron. The iron input to central California upwelling waters varies spatially and can be characterized by two end‐member regimes. One end member, which includes Monterey Bay and extending north to Pt. Reyes, is an iron‐replete regime where upwelling occurs over a relatively broad continental shelf that results in waters with high concentrations of dissolved and particulate iron (>10 nM) entrained together with high concentrations of nitrate and silicic acid. In these iron‐replete regions, extensive blooms of large diatoms deplete macronutrient concentrations, which results in correspondingly high chlorophyll a concentrations. The other end member, located to the south of Monterey Bay off the Big Sur coast, is an iron‐deplete regime where upwelling is focused offshore of a narrow continental shelf. Upwelled waters in the Big Sur region are characterized by low dissolved and particulate iron concentrations (

Pelagic—benthic coupling in the abyssal eastern North Pacific: An 8‐year time‐series study of food supply and demand - Kenneth Jr. L. Smith; Ronald S. Kaufmann; Roberta J. Baldwin; A. F. Carlucci (Limnology and Oceanography, 2001)
An 8‐yr time‐series study of the trophic coupling between a pelagic food supply and its utilization by the sediment community was conducted at 4,100‐m depth in the eastern North Pacific between 1989 and 1998. Supply of sinking particulate organic carbon (POC) and particulate total nitrogen (PTN) was estimated from collections made with sediment traps moored at 3,500‐ and 4,050‐m depth (600 and 50 m above bottom). Sediment community oxygen consumption (SCOC), an estimate of aerobic utilization of organic matter, was measured in situ. POC and PTN fluxes at both depths declined significantly from October 1989 through 1996 then increased in 1998. Organic carbon : total nitrogen (C : N) of the sinking particulate matter fluctuated ~10 throughout the study, except for a major peak (84.8) at 50 m above bottom in summer 1995, indicating lateral advection of organic material of terrestrial origin. POC: SCOC declined progressively over the first 7 yr, from a high of 0.99 in 1989–1990 to 0.22 in 1995–1996. In 1998, there was an increase in POC: SCOC to 0.43, suggesting that the food deficit was reduced by an increase in sinking flux. A continuing deficit in food supply cannot be sustained without ultimately affecting the structural and functional characteristics of the sediment community. The importance of undersampling by sediment traps, lateral advection of marine and terrestrial organic matter from the continental slope and shelf, and dissolved organic matter is evaluated. These other sources of nutrients for benthic organisms may be important in explaining some of the observed discrepancy between supply and demand in the abyssal Pacific. Decadal‐scale climate variations that influence marine primary production and terrestrial discharges into the ocean may be extremely important in understanding biogeochemical processes in the deep sea.

Anxiolytic effects of kava extract and kavalactones in the chick social separation-stress paradigm - Kenyatta K. Smith; H. Ranjith W. Dharmaratne; Matt W. Feltenstein; Susan L. Broom; J. Todd Roach; N.P. Dhammika Nanayakkara; Ikhlas A. Khan; Kenneth J. Sufka (Psychopharmacology, 2001)

Steady-State and Time-Resolved Fluorescence Polarization Behavior of Acenaphthene - Trevor A. Smith; David J. Haines; Kenneth P. Ghiggino (Journal of Fluorescence, 2000)

Immunolocalisation of BPTI-like serine proteinase inhibitory proteins in mast cells, chondrocytes and intervertebral disc fibrochondrocytes of ovine and bovine connective tissues. An immunohistochemical and biochemical study - James Melrose; Susan Smith; Kenneth Rodgers; Chris Little; Daniel Burkhardt; Peter Ghosh (Histochemistry and Cell Biology, 2000)

Transcriptional profiling of human microvascular endothelial cells in the proliferative and quiescent state using cDNA arrays - Hua-Tang Zhang; Michael Gorn; Kenneth Smith; Andrew P. Graham; Kelvin K.W. Lau; Roy Bicknell (Angiogenesis, 1999)

Lens epithelial proliferation cataract in segmental trisomy involving mouse Chromosomes 4 and 17 - Richard S. Smith; Kenneth R. Johnson; Norman L. Hawes; Belinda S. Harris; John P. Sundberg; Muriel T. Davisson (Mammalian Genome, 1999)

Behaviour and Impact of Cow Slurry Beneath a Storage Lagoon: 1. Groundwater Contamination 1975–1982 - Paul J. A. Withers; Hamish G. McDonald; Kenneth A. Smith; Colin G. Chumbley (Water, Air, & Soil Pollution, 1998)

Heliobacterium chlorum: cell organization and structure - Kenneth R. Miller; Jules S. Jacob; Ursula Smith; Stephen Kolaczkowski; Michael K. Bowman (Archives of Microbiology, 1986)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)